Comparison between angiotensin-converting enzyme inhibitor and angiotensin receptor blocker after percutaneous coronary intervention. (1st May 2020) - Ann, Soe Hee; Strauss, Martin H.; Park, Gyung-Min; Han, Seungbong; Yang, Yujin; Kim, Yong-Giun; Won, Ki-Bum; Kim, Shin-Jae; Lee, Sang-Gon; Cho, Young-Rak; Kim, Dae-Won; Park, Mahn-Won; et al.
Abstract: Background: The inhibitors for renin-angiotensin-aldosterone system (RAAS) have different mechanisms of action in coronary artery disease (CAD). This study sought to compare the clinical outcomes between angiotensin-converting enzyme inhibitors (ACEI) and angiotensin receptor blockers (ARB) therapy in patients with CAD undergoing contemporary percutaneous coronary intervention (PCI). Methods: Based on the National Health Insurance claims data in South Korea, patients aged 18 years or older who had undergone PCI between July 2011 and June 2015 were enrolled. The study participants were classified either as patients with acute myocardial infarction (AMI, n  = 21, 747) or angina ( n  = 28, 708). And according to the post PCI discharge medications, patients were categorized into ACEI and ARB therapy groups. The primary endpoint was all-cause death, and the two groups were compared using a propensity-score matching analysis. Results: The study population had a median follow-up of 2.2 years (interquartile range, 1.2–3.2). In the propensity-score matched AMI group (8341 pairs), the occurrence of all-cause death was significantly lower in the ACEI group than in the ARB group (hazard ratio [HR] of ACEI, 0.823; 95% confidence interval [CI]: 0.715–0.947; p  = 0.006). In the propensity-score matched angina group (10, 878 pairs), there was no difference in the incidence of the primary endpoint between the ACEI and ARB groups (HR of ACEI, 1.113; 95% CI: 0.986–1.257; p  = 0.084). Conclusions: In this nationwide Korean cohort study, ACEI therapy in patients with AMI and concomitant PCI showed a significant reduction in all-cause mortality rates when compared to that with ARB therapy. Highlights: Blockade of renin-angiotensin-aldosterone system is important in coronary disease. Angiotensin-converting enzyme inhibitors are recommended as a first line therapy. Angiotensin receptor blockers are recommended as a second line, for intolerance. First line therapy showed lower mortality rates in acute myocardial infarction.